Participación en el mercado de Automóvil Club del Ecuador Aneta de la ciudad de Babahoyo periodo 2022. - Contreras Cavero, Diana Stefany (2023)
The purpose of this case study is to make known the market share of Automobile Club del Ecuador ANETA so that this institution can correct deficiencies, thus achieving the main objective which is to identify the factors that affect the market share of the institution to know them and overcome them. For this, it is necessary for the institution to continuously execute marketing strategies and monitor them. This case study is also linked to the participation of the graduate in the business internships carried out at ANETA, so the problems of the institution were known in a timely manner. To know the current situation of the ANETA Institution, the descriptive level of research was used and through the use of techniques and instruments such as surveys and measurement of market share, it was possible to obtain pertinent information that resulted in information about consumer tastes. to improve according to their suggestions. Thanks to the measurement of market share, it was also obtained that the institution must improve its promotional and marketing strategies in order to capture the attention of consumers and achieve an advantage over the competition. The case study as a final objective will recommend digital strategies, establishing detailed information on what must be improved in the institution to attract the attention of clients and achieve a greater market share, showing what aspects must be changed to make itself known to the young public by making use of social networks to attract more consumers and thus increase sales.